Front Pages IJReSES Vol. 13, No. 2(2016) - Editorial Journal (BRIN, 2016)
Front Pages IJReSES Vol. 13, No. 2(2016)Â Â *Note:Â This cover is a revision of the Peer Reviewers section of the cover that was uploaded on May 26, 2017